Utilización de gallinas enteras, crudas o cocidas en la alimentación de cerdos de levante-ceba - Reyes G.; Sanmartín C. L.; Dávila L. M. (Acta Agronómica)
At the facilities of "El Verdal" poultry farm, located 1.6 miles away from Cali in the road to Jamundí, Valle del Cauca department, one research was conducted using 20 crossbred Yorkshire x Landrace pigs with 22 kg average initial weight, which were 127 days until they reached an average final weight of 86.4 kg. They were distributed at random in three treatments with different number of replications (one for the control and two for the experimental). The treatments were as follows: Boiled hens + Energy supplement (T1), Raw hens + Energy supplement (T2)and Control or Commercial type feed according to phase (T ). The main aim of this experiment was to look for the biological and economical feasibility of using whole hens (plus supplement) comming from the normal daily mortality or discard, from a commercial poultry farm, as an alternative feeding source for growing finishing pigs. There were no statistical significant differences for daily weight gain, feed efficiency and feed consumption. There was a slight higher feed consumption (dry matter) for T3 (2.14 kg), followed for TI and T2 (2.13 kg). In relation to daily weight gain, T) had 515 g; TI' 507 g and T2, 497 g. The best feed efficiency was for T) (4.16), followed for TI (4.2) and for T2 (4.28). Related to the economical results, higher feeding costs were for T) ($ 52 167) and lower for TI and T2 ($ 42 167). Profits for fattening pig were better for TI ($ 15 415), followed for T2 ($ 14587) and for T3 ($ 8208). En las instalaciones de la granja avícola "El Verdal", localizada a un Km del perímetro urbano en la vía que de Cali conduce a Jamundí, Valle del Cauca se realizó un trabajo de investigación empleando 20 cerdos cruzados de las razas Yorkshire y Landrace, con un peso inicial promedio de 22 kg, los cuales fueron llevados hasta un peso final promedio de 86.4 kg a los 127 días y se distribuyeron al azar en tres tratamientos con diferente número de repeticiones (dos para los experimentales y una para el testigo). Los tratamientos fueron: gallinas cocidas + suplemento energético (T1), gallinas crudas + suplemento energético (T2) y como testigo, el concentrado comercial según fase (T3). La finalidad del ensayo fue comprobar la factibilidad biológica y económica del empleo de gallinas enteras suplementadas, provenientes de la mortalidad normal diaria o el despaje en una avícola comercial, como fuente alternativa de alimentación en cerdos de Levante-Ceba. No hubo diferencias estadísticas significativas para ganancia diaria, consumo de alimento y conversión alimenticia. Se notó un leve mayor consumo en m. seca en T3 (2.14 kg) seguido de T1 y T2 (2.13 kg). El T3 tuvo mayor ganancia diaria (515 g), seguido del TI (507 g) y del T2 (497 g). La mejor conversión alimenticia la tuvo T3 (4.16), seguida de TI (4.2) y luego de T2 (4.28). Los mayores costos en alimentación por cerdo los tuvo T3 ($ 52.167) y los menores TI y T2 ($42.167). En relación con utilidad por cerdo cebado, el mejor resultado fue para T1 ($15.415), seguido de T2 ($14.587) y luego por T3 ($8.208).